2009
DOI: 10.4317/medoral.15.e52
|View full text |Cite
|
Sign up to set email alerts
|

Implant treatment in patients with osteoporosis

Abstract: Osteoporosis is very common, particularly in post-menopausal women and is characterized by a decrease in bone mass and strength. Osteoporosis also affects the jawbone and it is considered a potential contraindication to placement of dental implants. The present paper reviews the literature regarding the effect of osteoporosis on osseointegration of implants. Experimental models have shown that osteoporosis affects the process of osseointegration, which can be reversed by treatment. However, studies in subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 15 publications
1
61
0
8
Order By: Relevance
“…Deficiency of this vitamin affected gene expression during and after osseointegration; the expression of collagen I and II increased in the presence of titanium 35 . In a review study conducted by MelladoValero et al 34 on the effect of osteoporosis on the osseointegration of implants, showed that osteoporotic individuals had no differences in implants survival compared with healthy individuals; therefore, osteoporosis could not be considered contraindication for implant placement, and the steps to be taken before starting a surgical implant would be not different from people without osteoporosis.…”
Section: Methodsmentioning
confidence: 99%
“…Deficiency of this vitamin affected gene expression during and after osseointegration; the expression of collagen I and II increased in the presence of titanium 35 . In a review study conducted by MelladoValero et al 34 on the effect of osteoporosis on the osseointegration of implants, showed that osteoporotic individuals had no differences in implants survival compared with healthy individuals; therefore, osteoporosis could not be considered contraindication for implant placement, and the steps to be taken before starting a surgical implant would be not different from people without osteoporosis.…”
Section: Methodsmentioning
confidence: 99%
“…Postmenopausal osteoporosis is a skeletal disease characterized by reduced bone mass and deterioration of the bone micro-architecture, mainly due to increased bone resorption elicited by estrogen deficiency [3]. This medical condition is an important risk factor for implant failure in orthopedic and oral surgery, both during the healing as well as during the implant functional status [4][5][6]. Anti-resorption drugs, such as bisphosphonates, selective estrogen receptor modulators, and hormone therapy have been used to treat osteoporosis for years.…”
Section: Introductionmentioning
confidence: 99%
“…Review of the current literature reflects a limited, but growing, knowledge of the relative risks to dental implant treatment in patients receiving bisphosphonate medication [139,[170][171][172][173][174][175][176][177][178][179]. There have been several case reports and series that have evaluated implant failures in patients receiving intravenous bisphosphonate therapy [180], while other retrospective studies have indicated that there may be risks of osteopathology developing in patients receiving oral bisphosphonates and dental implant treatment [10][11][12][13][14].…”
Section: Bisphosphonates and Dental Implantsmentioning
confidence: 99%